Contemporary Issues in Natural Language Semantics: an interview with Gennaro Chierchia - Chierchia, Gennaro; Oliveira, Roberta Pires de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
Chierchia discusses his views on the frontiers of contemporary semantics: multidimensionality of meaning, alternative semantics, ‘mid level’ generalizations, the natural logicality of natural languages, the role of reference, and the place of new methodologies, i.e. lab-experiments.